Papillary muscle rupture after transcatheter aortic valve implantation. Issue 2 (23rd September 2020) - Morita, Yusuke; Endo, Akihiro; Tanabe, Kazuaki
Abstract: Catheter‐induced mitral regurgitation (MR) caused by mitral papillary muscle rupture can be a fatal complication of transcatheter aortic valve implantation (TAVI). We report a case involving an 89‐year‐old man who presented with symptomatic severe aortic stenosis. In addition, preoperative echocardiography showed accessory mitral valve tissue. Although moderate MR developed immediately after TAVI, severe MR caused by anterolateral papillary muscle rupture occurred 3 months after TAVI. As only a few case series have been published, our case report adds to the evidence base for this treatment strategy.